'I don't know where all the cutlery is': exploring materiality and homemaking in post-separation families. (12th February 2022) - Walker, Amy
ABSTRACT: This paper explores the ways in which home is experienced by children within post-separation families, who spend time within more than one parental home. To do so it draws on semi-structured interviews with fifteen young adults looking back on their childhood experiences. It argues that for these young people, home is a complex achievement, created and constrained, in part, through emotional encounters with domestic objects, interiors and furnishings. Resonating with previous studies which have emphasised the entanglement of family and home(un)making practices, it finds that children's family relationships are produced, communicated and undermined through the 'stuff' within their homes, creating feelings of inclusion and exclusion from their domestic environments. This paper, therefore, argues that domestic materialities are a significant means through which the (re)-and-(un)making of familial relationships in post-separation is performed; building on recent work within the emerging field of family geographies which has drawn attention to the importance of everyday materialities in the doing of family. Conclusions are thus drawn which suggest the value of such an approach to the interdisciplinary literature on post-separation and calls for more research into the various spatialities and materialities of the post-separation family are made.